To resist or to germinate? The effect of fire on legume seeds in Brazilian subtropical grasslands - Alessandra Fidelis; Luís Felipe Daibes; Aline Redondo Martins (Acta Botânica Brasílica, 2016)
Fire plays an important role in several grassland ecosystems in the world. Fire can trigger germination in several species, by breaking the physical dormancy of their seeds. Thus, we hypothesized that exposure to high temperatures during fire would break seed dormancy and enhance germination. We tested the effect of high temperatures on the germination of six species of legumes from Brazilian subtropical grasslands. We used heat shock experiments with the following treatments: 60, 90, 120 and 150ºC for one minute. Seeds were then placed to germinate for 60 days in 12/12 hours light/dark and 20/30ºC. Germination was generally low for all study species. Most species was not affected by heat shock treatments. However, Stylosanthes montevidensis was the only species that had its physical dormancy broken when exposed to 120ºC. The seeds of all the other species were neither stimulated nor killed by high temperatures. Although the exposure to high temperatures did not affect the germination of the study species (except for one), it also did not kill seeds, thereby showing that seeds are resistant to fire. Therefore, the rapid passage of fire in these grasslands is not sufficient to break the dormancy of most of the studied species of legumes.